2014
DOI: 10.2196/jmir.3346
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Cost-Effectiveness and Clinical Outcomes of a Fourth-Generation Synchronous Telehealth Program for the Management of Chronic Cardiovascular Disease

Abstract: BackgroundTelehealth programs are a growing field in the care of patients. The evolution of information technology has resulted in telehealth becoming a fourth-generation synchronous program. However, long-term outcomes and cost-effectiveness analysis of fourth-generation telehealth programs have not been reported in patients with chronic cardiovascular diseases.ObjectiveWe conducted this study to assess the clinical outcomes and cost-effectiveness of a fourth-generation synchronous telehealth program for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…The telehealth care system in this study is not only a health monitoring system, but also a tool that assists in decision making. Fortunately, our previous studies have shown that the Telehealth Center of the National Taiwan University Hospital has provided effective telehealth care for chronic cardiovascular disease patients and has reduced medical costs and the burden on caregivers [ 43 - 45 ]. A previous study has also indicated that the data analytics in the telehealth care system could assist clinicians at the point of care [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The telehealth care system in this study is not only a health monitoring system, but also a tool that assists in decision making. Fortunately, our previous studies have shown that the Telehealth Center of the National Taiwan University Hospital has provided effective telehealth care for chronic cardiovascular disease patients and has reduced medical costs and the burden on caregivers [ 43 - 45 ]. A previous study has also indicated that the data analytics in the telehealth care system could assist clinicians at the point of care [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies conducted non-randomised open intervention studies (36,37) . The remaining studies have used a retrospective observational study design (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) , a prospective observational study design (53)(54)(55)(56)(57) four of them were cohort (53)(54)(55)(56) , a pre post design (58)(59)(60)(61) , and one descriptive study (62) .…”
Section: Clinical Outcomementioning
confidence: 99%
“…The most common speciality reporting economic outcomes was paediatrics (n=7) (63)(64)(65)(66)(67)(68)(69) . Simple cost analysis was used by (n=14) (52,(63)(64)(65)(66)(67)(70)(71)(72)(73)(74)(75)(76)(77) studies measuring the cost avoidance, cost saving and added revenue. While (n=15) (27,30,35,58,68,69,(78)(79)(80)(81)(82)(83)(84)(85)(86) studies conducted a cost minimization analysis as a method to assess the economic benefits of telemedicine.…”
Section: Economicmentioning
confidence: 99%
“…The survey conducted during 2009-2010 in remote regions of the Brazilian state of Minas Gerais shows that the teleconsultations can avert 80.8% of referrals and 45.5% of transportation costs [14]. Many other studies also verified that telemedicine could greatly reduce the healthcare cost, shorten the waiting time, and improve the utilization efficiency of health resources [15][16][17][18].…”
Section: Introductionmentioning
confidence: 97%